Dealer breaks ground (Raton Range Raton, NM, 1985)
This article is about the ground breaking for Circle Chevrolet-Buick.
Newspaper article + photograph of Howard Lackey and John Lackey
Master list item #: 37
File location is in the Raton file Cabinet
Keywords: Lackey, Howard; Lackey, John; Circle Chevrolet-Buick; United Chevrolet-Toyota; Ground Breakings; Local Business; Dealerships; Raton, New Mexico; Trinidad, Colorado